Strategi PT. Holcim Indonesia, Tbk dalam Pemberdayaan Masyarakat Islam - Nuning Widya Hastuti; Dadang Kuswana; Indira Sabet Rahmawaty (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
The research as a purpose to know and analyzed the strategy and program was made by PT. Holcim Indonesia, Tbk for empowering the Islamic community. And know the implementation fund CSR PT. Holcim Indonesia, Tbk for society. This research form qualitative research used descriptive method. Technique collecting data used observation, interview, and documentation. The analysis data used by logic interpreter connected with the development of Islamic society context. The results of the research that strategy and program PT. Holcim Indonesia, Tbk make 5 pillars to develop of Islamic society that is economy, area, training and education, infrastructure and social, distribution implementation funds CSR take a procedure that is social mapping, organize media communication of society as transparency, the annual budget, make a program appropriate from each village, implementation of program and Monitoring and evaluation. The result of implementation and CSR PT. Holcim Indonesia, Tbk the society explain that satisfied till increase self-confidence to explain aspiration and able to compete, increasing public awareness to create the village economy environment.